On the occurrence of Branchinecta orientalis Sars, 1901 (Crustacea, Anostraca) in Algeria, with some ecological notes - Beladjal, Lynda; Amarouayache, Mounia (Zootaxa, 2023)
The first substantiated record of Branchinecta orientalis in Algeria is here reported. This species was found in a small freshwater pool (Jemot) in Oum El Bouaghi province, located in the High Plateaus of the Aurès region in North-East of Algeria. Details on biogeography, ecology and morphology of this Algerian population of the species are provided. In its Algerian occurrence locality, B. orientalis co-occurs mostly with Branchinecta ferox during autumn and spring but also with other large Branchiopoda with a maximum of 7 species occurring synchronically and 9 species in total.